Development of Early Childhood Character Values Through Exemplary Habituation in Schools - Rahayu Bakari, Sri; Huljanah Lakamaru, Miftah; Basumbang, Nurhasanah; Novita Sayi, Sri (Educationist: Journal of Educational and Cultural Studies, 2022)
This study aims to determine the development of early childhood values through habituation in schools. Character education for early childhood is intended to instill values in Understanding the development of affective aspects in a child that are one of the factors for achieving good results in the educational process, and can form a good child's personality so that later when they grow up, they will become good people and have a noble character to benefit their fellow human beings and their environment. The preparation of the syllabus / RPPH, especially in kindergarten, is usually carried out to make implementation in instilling character values in early childhood This research uses a qualitative approach with preliminary research observation methods, deepening the cultivation of character education values and their implementation through example and habituation. The results show that the process of implementing character value education in the Playgroup of Al- Fajril Ulum District School in South City, Gorontalo City can be seen from the approach between teachers and children through Disciplinary and multidisciplinary. This approach is carried out to improve the development of children's character values in the learning process such as morals, honesty, and manners. Each indicator of character education is indicated by learning strategies and methods that reflect the value of each character. The learning method in question can be in the form of assignments and learning practices as well as habituation so that the values of character education can be implemented.